Turkish validity and reliability of the Personal Impact of Epilepsy Scale - Ozer, Zulfunaz; Turan, Gulcan Bahcecioglu; Yildiz, Esra (Academic Press Inc Elsevier Science, 2021)
Aim: This study evaluated the validity and reliability of the Turkish Personal Impact of Epilepsy Scale (PIES). Materials and Method: This methodological study was carried out at a university hospital in Erzurum, eastern Turkey between January and April 2021. The data were collected from 126 patients who agreed to participate in the study within these dates via face-to-face interviews, a personal information form, and the Turkish PIES. The PIES consists of 25 items, scored between 0 and 4, and three subscales. The scale itself is a 5-point, Likert-type scale. Following the scale's translation process, its content and construct validity were evaluated. Exploratory and confirmatory factor analysis were conducted for construct validity and item analysis, and internal consistency analysis took place to confirm the scale's reliability. Results: As a result of the evaluations and analyses, the Turkish PIES's content validity index was 0.94. In the exploratory analysis, the scale's total variance rate was 70.82%. The Cronbach's alpha value of the Seizures subscale was 0.728, that of the Medication Side Effects subscale was 0.947, for the Comorbidities subscale it was 0.929, and the total scale's Cronbach's alpha value was 0.954. The results of the EFA (Exploratory Factor Analysis) and CFA (Confirmatory Factor Analysis) showed that the Turkish PIES, per its 25 items and three-factor structure, is a sufficient measurement instrument. Good fit index values were also obtained as a result of the CFA. Conclusion: The Turkish version of the PIES is a valid and reliable instrument to evaluate the effects of seizures, medication side effects, mood/social state, and quality of life of patients with epilepsy. (C) 2021 Elsevier Inc. All rights reserved.
Keywords: Epilepsy impact; Patient; Reliability; Validity